“ExBoxes” with Fluorene and Carbazole Units. Synthesis, Structure Determination, and Formation of Host–Guest Complexes - Căta, Lidia; Stroia, Ioan; Nicolay, Cyril; Hādade, Niculina Daniela; Terec, Anamaria; Barboiu, Mihail; Grosu, Ion (Synthesis, 2025)
The synthesis and the structural characterization of two new extended “boxes” exhibiting carbazole or fluorene units are reported. The ability of these tetracationic host molecules to form complexes with electron-rich guests was evaluated by computational methods and investigated by NMR and MS experiments.
Keywords: ExBoxes; Carbazole and fluorene derivatives; Host–guest complexes; NMR titrations; Molecular modeling